Dynamic Spectrum Allocation Scheme for Heterogeneous Network - Hasan M.K.; Ismail A.F.; Islam S.; Hashim W.; Pandey B. (Springer New York LLC, 2023)
Cochannel interference; Complex networks; Femtocell; Heterogeneous networks; Mobile telecommunication systems; Multiple access interference; Orthogonal frequency division multiplexing; Cochannel interference (CCI); Dynamic spectrum allocations; Heterogeneous network (HetNets); MRaSD; OFDMA; Orthogonal frequency division multiple access; Power allocation algorithms; Spectral efficiencies; Frequency division multiple access